การพัฒนาแบบวัดภูมิต้านทานทางอารมณ์และจิตใจเชิงสถานการณ์ สำหรับนักศึกษาปริญญาบัณฑิต โดยใช้เทคนิคแผนผังกลุ่มเชื่อมโยง การสัมภาษณ์แบบ MMI และการวิเคราะห์พหุลักษณะ-พหุวิธี 2 ระดับ - วราพร เอราวรรณ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2010)
The objectives of the research were to develope Resilience Quotient Situation test for undergraduate students using affinity diagram and multiple mini interviews, and validate the reliability convergent validity and discriminant validity at student level and group level by 2 level multitrait-multimethod analysis ( 5 traits 2 method at 2 level). The sample were 1,611 undergraduate students from 19 universities using the multistage random sampling. Data analysis based on descriptive statistic, the Index of consistency, the Pearson s product moment correlation, the Cronbach s alpha coefficients and exploratory factor analysis using SPSS for Windows. The second order confirmatory factor analysis and 2 level multitrait-multimethod analysis was carried out using Mplus version 5.21. The results of the research showed that: (1) The difficult index of 44 RQ situation tests varied from 0.168 to 0.535, Cronbach s alpha reliability at 0.892. (2) The results of exploratory factor analysis was found that five factors. (3) The second order confirmatory factor analysis of RQ measurement model fit quite well with empirical data set (CFI= 0.984, TLI= 0.980, RMSEA= 0.021, SRMR= 0.021 and X² /df= 1.68). (4) The 2 level multitrait-multimethod analysis of model fit with empirical too (CFI=0.990, TLI = 0.977, RMSEA = 0.031, SRMRw= 0.006, SRMRb= 0.134 and X²/df=2.56). The statistical analysis indicated that, the convergent validity, reliability and discriminant validity of RQ situation test at group level higher than student level.